Peran Komite Sekolah Dalam Pembinaan Karakter Peserta Didik di SMA Negeri 1 Aceh Barat Daya (International Forum of Researchers and Lecturers, 2024)
The character of students at school is decreasing, especially the students. There are some students who are lazy about attending lessons, there are some students who skip school, there are students who do not take part in learning activities in a particular subject, and also the indifferent attitude of students in paying attention to the explanation of the teacher who is teaching in front of the class. Therefore, the role of the school committee is very necessary by collaborating with the school to find ways to guide students in character building. This research aims to determine the role of committees in developing student character as well as the obstacles faced by committees and schools in developing student character. The research method uses qualitative research, through observation, interview and documentation data collection techniques. Research subject; Mr. Husni as the School Committee, Erda Wika as Deputy Head of Public Relations and 3 parents, namely Mr. Hendri, Mrs. Evi Aidar and Mrs. Mariana. Research results: (1) Committee planning can be seen in determining tasks and goals in accordance with what is to be achieved. The committee also discusses the planning of the program that will be implemented, the planning is discussed together with the school community and parents/guardians of students using various delivery methods, where in the planning there is the formulation of objectives, formulating tasks and developing work strategies. (2) The Committee regulates the strategy for developing the character of students in accordance with the work agenda as discussed in the work agenda directly at school meetings or general meetings which also include parents, guardians/students. (3) The obstacles experienced occur more often outside the school environment, due to the lack of parental supervision of children so that they are more likely to enter into free association. Meanwhile, in terms of funding, the obstacle experienced by the committee is that most parents of students are economically weak, because a weak economy can also be a problem or obstacle for students who want to go to school.